De novo hepatocellular carcinoma 18 years after liver and small bowel transplantation in a one‐year‐old pediatric patient. (25th August 2020) - Bryan, Nathan; Zandieh, Arash; Kallakury, Bhaskar; Kaufman, Stuart; Yazigi, Nada; Girlanda, Rafaele; Hawksworth, Jason; Fishbein, Thomas; Matsumoto, Cal; Kroemer, Alexander; Khan, Khalid
Abstract: De novo HCC following transplantation in a child is a rare occurrence. Even within the adult liver transplantation population, there are a limited number of published cases. In this report, we present a case of de novo HCC found in a child, post‐multivisceral transplantation. A 19‐year‐old boy, at the age of one, received liver and small bowel transplantation due to short gut syndrome secondary to midgut volvulus and total parenteral nutrition‐associated liver disease. Eighteen years later, he was found to have a large mass involving the right hepatic dome consistent with HCC. To the best of our knowledge, this is the second reported case after gut transplantation and the third case post‐liver transplantation in the pediatric population.